Hegemoni Maritim dan Militer Kerajaan Sriwijaya di Kawasan Asia Tenggara Abad 7-10 M - Nanda Julian Utama (Yupa: Historical Studies Journal, 2021)
This article discusses the Srivijaya kingdom during its golden period. The main issue raised was how the Sriwijaya Kingdom was trying to build its maritime and military power between the 7-10 century AD. In its heyday, Srivijaya was able to control most of the western region of Southeast Asia. The extent of this kingdom's power requires it to have a strong base in maritime and military aspects. Although the center of Sriwijaya in Palembang is not a coastal city, it can control the shipping network, especially around the Malacca Strait. There are at least three things that can be seen to describe the position of Srivijaya in its golden era, namely: the ability of the center to be able to control the vassal area, the ability to consolidate military power, especially the control of the sea people, and cultural ties that bind, for example in the magical aspect between kings. With all the people. This paper will use various relevant sources, including reviewing various writings and publications about Sriwijaya from the previous period.